Penyuluhan HKI Dalam Perspektif HAM di Distrik Arso Timur Kabupaten Keerom - Pelupessy, Eddy; Mambaya, Marthinus; Sawen, Kristina; Tanati, Daniel; Palenewen, James Yoseph (Yayasan Daarul Huda Kruengmane, 2024)
This service was carried out with the title IPR Counseling in a Human Rights Perspective in the East Arso District, Keerom Regency. This activity was carried out because the partners did not understand IPR from a human rights perspective in order to guarantee legal certainty, so that with the expertise possessed by the service team, they could carry out legal counseling in a manner The aim is to provide a link between IPR and Human Rights as well as legal protection for creative works in the fields of science, arts and literature or capabilities in the field of technology, creative works or inventions. The method of implementing this service is carried out by means of legal education through lectures and discussions which were held on Thursday, November 23 2023, which was held in East Arso District, Keerom Regency. This activity begins with preparation and coordination, then presentation of material by providing knowledge to partners regarding the relationship between IPR and Human Rights as well as legal protection for creative works in the fields of science, art and literature or capabilities in the field of technology, copyrighted works or inventions. The output of this service is to provide understanding and knowledge to partners about the relationship between IPR and Human Rights as well as legal protection for someone's creative work and Intellectual Property Rights are rights that originate from the results of creative activities, the ability of human thought which is expressed to the general public in various ways. form, which has benefits and is useful in supporting human life. Apart from that, it also has economic value which is a real form of the ability of intellectual work, which can be in the fields of science, arts and literature as well as in the field of technology.